Cain v. Abel : a Jewish courtroom drama - Ornstein, Dan (University of Nebraska Press ; The Jewish Publication Society, 2020)
"Come, take your seat as a juror on the Cain v. Abel trial. The Prosecution and Defense attorneys (angels from Jewish legend) will soon call Cain, Abel, Sin, Adam, Eve, great commentators of Jewish tradition, and God to the witness stand to unpack the emotional, societal, and spiritual influences underlying the world's first murder"--